Kahoot! In English Classroom to Improve Reading Students in Madrasah Aliyah Jamiat Kheir - Ardini, Fauziah; Burhayani, Burhayani (Department of English Language Education, Universitas Muhammadiyah Purworejo, Indonesia, 2024)
This research presents the results of a small survey study involving 22 high school students at an international educational institution, regarding their experiences in learning languages using Kahoot!, an online quiz game platform. The research sample consisted of 22 students (13 female and 9 male) from Madrasah Aliyah Jamiat Kheir, Central Jakarta, in the period November 2023 to July 2024. This research used quantitative and experimental methods for data collection. The collected quantitative data was analyzed statistically using descriptive statistical methods. Analysis shows that the majority of students responded positively to the use of Information and Communication Technology in classroom learning, especially in the use of Kahoot! Most students felt that Kahoot! increasing their motivation and involvement in the learning process, as well as helping them understand the material better through an interactive and fun approach. This research also emphasizes the important role of teachers in preparing and implementing learning technology effectively. Teachers need to prepare well and use appropriate practices based on their experience and knowledge. Understanding effective reading methods is very important to improve the quality of learning in Indonesia. The results of this research show that implementing appropriate learning technology, such as Kahoot!, can significantly improve students' reading abilities. Additionally, this research highlights the importance of training and professional development for teachers in the use of educational technology. With adequate training, teachers can be more effective in integrating ICT into the curriculum, creating a more dynamic and productive learning environment. This research provides evidence that the use of technology tools such as Kahoot! can be an effective strategy for improving the quality of education, especially in teaching English in Indonesia.